PENGEMBANGAN WORKSHEET TEMATIK-INTEGRATIF PADA MATA PELAJARAN IPA TERPADU UNTUK MENUMBUHKAN LITERASI SAINS SISWA - Hunaepi Hunaepi; Muhali Muhali; Saiful Prayogi (Bioscientist : Jurnal Ilmiah Biologi, 2013)
This research was conducted to increase students' science literacy. Specific objectives can be specified in detail: 1) describing the feasibility of integrative thematic worksheets of integrated science subjects developed; 2) measuring students' science literacy abilities after completion of the Integrated IPA learning by using thematic-integrative worksheet materials; and 3) to describe students' responses to integrated IPA learning by using thematic-integrative worksheet materials. The teaching materials produced in the form of thematic-integrative worksheets as supporting learning process that can cultivate science literacy science ability. The thematic-integrative worksheets that have been developed meet the criteria of validity and according to the expert and the results of the experiments show that the thematic-integrative worksheet material can support effective learning. The validity level of all learning devices used is in a valid category and is appropriate for use. The results of the first trial showed that the students' science literacy skills in the first trial scored an average of 79.2 and for the second trial got an average of 82.2 with a very high category. Based on the results of the analysis it was found that the thematic-integrative worksheets developed can develop students' science literacy and deserve to be used.